Glass fiber reinforced plastic and preparation method thereof
By introducing glass fiber and modified materials into PVC plastics, glass fiber reinforced plastics are formed, which solves the problem of insufficient performance of PVC plastics at low and high temperatures, and achieves high toughness and thermal stability of the material.
Patent Information
- Application Number
- CN202411805617.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-03
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-18
AI Technical Summary
Polyvinyl chloride (PVC) plastics are prone to brittle under low temperature environments and tend to deform and age at high temperatures, resulting in insufficient low temperature resistance and high temperature resistance.
Using glass fiber reinforced plastic, by reasonably mixing polyvinyl chloride, modified ethylene-vinyl alcohol copolymer, modified phenolic resin, glass fiber, modified mica powder, kaolin, antioxidants and coupling agents, Form a high-performance glass fiber reinforced plastic.
It significantly improves the toughness and thermal stability of PVC plastics, enhances its impact resistance and tensile strength in high and low temperature environments, and ensures that the performance of the material remains good under high temperature conditions.
Smart Images

Figure BDA0005179139090000141
Abstract
Description
[0001] This application claims priority to Chinese patent application number: 202410409233.0, filed on April 3, 2024, entitled “A glass fiber reinforced plastic and a method for preparing the same”, the entire text of which is hereby incorporated by reference. Technical Field
[0002] The invention relates to the technical field of polyvinyl chloride composite materials, and in particular to a glass fiber reinforced plastic and a preparation method thereof. Background Art
[0003] Polyvinyl chloride (PVC) was once the world's largest-volume general-purpose plastic and is widely used in building materials, industrial products, daily necessities, floor coverings, floor tiles, artificial leather, pipes, wires and cables, packaging films, bottles, foaming materials, sealing materials, fibers, etc.
[0004] PVC is a white powder with an amorphous structure, a small degree of branching, a glass transition temperature of 77-90°C, and begins to decompose at around 170°C. It will decompose at temperatures above 100°C or after long-term exposure to sunlight. Therefore, PVC plastics tend to become brittle at low temperatures and are prone to deformation and aging at high temperatures. Therefore, the low-temperature and high-temperature resistance of PVC plastics need to be further improved.
[0005] CN117586589A discloses a special pellet for high temperature and impact resistant rigid polyvinyl chloride corrugated pipe and its preparation method, the pellet comprises: 100 parts of PVC resin, 40-60 parts of heat resistant modified resin, 5-8 parts of calcium zinc-tin composite heat stabilizer, 10-20 parts of toughening agent, 2-4 parts of lubricant, 5-8 parts of processing modifier, 1-2 parts of natural paraffin release agent. It mainly improves the high temperature and impact resistance of polyvinyl chloride by mixing polyvinyl chloride with various resins, and the method has limited improvement on the plasticity of the material.
[0006] CN117362868A discloses a low-temperature resistant, high-strength, high-wear-resistant polyvinyl chloride nanocomposite material and its preparation method and application, comprising the following raw materials in parts by weight: 100 parts of PVC resin, 1.3-5 parts of stabilizer, 0.5-1.5 parts of internal lubricant, 0.5-1.5 parts of external lubricant, 1.5-3.5 parts of processing aid, 1-12 parts of MBS resin, 0-8 parts of CPE resin, 5-15 parts of filler, and 5-10 parts of modified nano alumina. The material improves the low-temperature toughness and wear resistance of polyvinyl chloride. However, this method adds more inorganic additives and fillers, and the dispersibility between the inorganic filler and polyvinyl chloride is poor, which will cause a decrease in mechanical properties.
[0007] Therefore, it is necessary to continue to develop new polyvinyl chloride materials to obtain better low-temperature and high-temperature resistance performance improvements. Summary of the invention
[0008] In view of the above technical problems, the purpose of the present invention is to provide a glass fiber reinforced plastic and a preparation method thereof, which can improve the high and low temperature resistance of PVA and enhance its toughness and thermal stability without reducing the mechanical properties.
[0009] The invention provides a glass fiber reinforced plastic. The glass fiber reinforced plastic is prepared from the following raw materials in parts by weight: 60-80 parts of polyvinyl chloride, 10-20 parts of modified ethylene-vinyl alcohol copolymer, 10-20 parts of modified phenolic resin, 20-40 parts of glass fiber, 1-10 parts of modified mica powder, 1-10 parts of kaolin, 0.5-1 parts of antioxidant and 1-2 parts of coupling agent.
[0010] Furthermore, the preparation method of the modified phenolic resin comprises:
[0011] (1) Add phenol and an acidic catalyst into a reaction vessel, heat to 90-100° C., and stir until completely dissolved;
[0012] (2) adding aldehyde and chitosan to the above solution, and after addition, reflux reaction for 2-5 hours;
[0013] (3) The reaction solution is subjected to reduced pressure distillation to obtain a modified phenolic resin.
[0014] In the above technical solution, chitosan is a product of the natural polysaccharide chitin with some acetyl groups removed, and has multiple physiological functions such as biodegradability, biocompatibility, non-toxicity, antibacterial, anti-cancer, lipid-lowering, and immune enhancement. Chitosan molecules have multiple hydroxyl groups and amino groups, which can be well combined with phenolic resin to obtain super-large molecules, which not only improves the compatibility of phenolic resin, but also has many characteristics of chitosan.
[0015] Preferably, the phenol is phenol or cresol.
[0016] Preferably, the acidic catalyst comprises at least one of oxalic acid, acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, phosphonic acid, benzenesulfonic acid and p-toluenesulfonic acid.
[0017] Preferably, the aldehyde is formaldehyde or acetaldehyde.
[0018] Preferably, the viscosity average molecular weight of the chitosan is 10000-50000 kDa and the degree of deacetylation is above 85%.
[0019] Furthermore, the preparation method of the modified ethylene-vinyl alcohol copolymer is: melt-blending LDH and ethylene-vinyl alcohol copolymer to obtain the modified ethylene-vinyl alcohol copolymer.
[0020] In the above technical solution, the surface of the LDH layer has a large number of hydroxyl groups, which can form hydrogen bonds with the hydroxyl groups of the ethylene-vinyl alcohol copolymer and firmly bond to the surface of the ethylene-vinyl alcohol copolymer.
[0021] Preferably, the amount of LDH added to the modified ethylene-vinyl alcohol copolymer is 0.8-3%, and the particle size of the LDH is 1-100 nm.
[0022] More preferably, the particle size of the LDH is 20-50 nm.
[0023] In the above technical solution, within the appropriate range of LDH particle size and addition amount, LDH can be well combined with the surface of the matrix, while improving the mechanical properties, barrier properties and flame retardancy of the PVC material.
[0024] Preferably, the LDH includes at least one of Mg / Al-LDH, Mg / Zn / Al-LDH, and Zn / Al-LDH.
[0025] Furthermore, the modified mica powder is silane-modified mica powder.
[0026] Preferably, the silane is one or more of hexadecyltrimethoxysilane, dodecyltrimethoxysilane, aminopropyltriethoxysilane and propyltrimethoxysilane.
[0027] In the above scheme, silane-modified mica can greatly improve the compatibility between inorganic mica powder and resin, and reduce the problem of poor dispersion of inorganic fillers in the resin causing a decrease in mechanical properties.
[0028] Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a phosphite antioxidant, and a thioester antioxidant, or a combination of at least two thereof.
[0029] Preferably, the coupling agent is one or both of vinyltrimethoxysilane and vinyltriethoxysilane.
[0030] The present invention also provides a method for preparing glass fiber reinforced plastic, comprising the following steps:
[0031] S1, mixing polyvinyl chloride, modified ethylene-vinyl alcohol copolymer and modified phenolic resin to obtain a mixed resin;
[0032] S2, mixing the mixed resin and glass fiber, modified mica powder, kaolin, coupling agent, and antioxidant uniformly, melt-blending and extruding through a twin-screw extruder to obtain the glass fiber reinforced plastic.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention uses nano LDH to modify the ethylene-vinyl alcohol copolymer. The surface of the LDH layer has a large number of hydroxyl groups, which can form hydrogen bonds with the hydroxyl groups of the ethylene-vinyl alcohol copolymer and firmly bond to the surface of the ethylene-vinyl alcohol copolymer. The LDH has a lamellar structure and can form a consistent and continuous orientation during the blending process. The addition amount and particle size range of the LDH are controlled to effectively improve the comprehensive barrier properties, mechanical properties and flame retardancy of the ethylene-vinyl alcohol copolymer.
[0035] The present invention uses chitosan to modify the phenolic resin, which can significantly enhance the toughness of the phenolic resin, not only improves the compatibility between the phenolic resin and other raw materials, but also has many characteristics of chitosan.
[0036] In the present invention, polyvinyl chloride, modified ethylene-vinyl alcohol copolymer, and modified phenolic resin are mixed as a matrix, which can improve the plasticity of polyvinyl chloride, reduce its low-temperature brittleness, significantly improve its toughness, and have better impact resistance. The surfaces of modified ethylene-vinyl alcohol copolymer and modified phenolic resin contain a large number of active groups such as hydroxyl and amino groups, and the surface of chitosan is positively charged. The surface of the LDH layer in the modified ethylene-vinyl alcohol copolymer is also positively charged, which can adsorb glass fiber and firmly bind the glass fiber, greatly reduce the brittleness of the glass fiber, and improve its toughness. The mixed matrix of polyvinyl chloride, modified ethylene-vinyl alcohol copolymer and modified phenolic resin is mixed with glass fiber, modified mica powder, kaolin, antioxidant and coupling agent, which can improve the strength and thermal stability of plastics and improve their high temperature resistance.
[0037] In summary, the present invention selects the appropriate proportion of polyvinyl chloride, modified ethylene-vinyl alcohol copolymer, modified phenolic resin, glass fiber, modified mica powder, kaolin, antioxidant and coupling agent by carefully selecting the raw material composition and optimizing the content of each raw material, which not only fully exerts the advantages of each other, but also complements and promotes each other, thereby improving the quality stability of the product. The prepared PVC plastic has excellent mechanical properties such as tensile strength, good high and low temperature resistance, and the mechanical properties such as tensile strength and impact strength are still maintained well under high temperature conditions. DETAILED DESCRIPTION
[0038] The specific implementation methods of the technical solution of this specification are further described below through specific examples. These examples are for the purpose of describing the technical solution in detail, rather than for limiting the technical solution. Based on the examples in this specification, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this specification.
[0039] Polyvinyl chloride, SG-5 type PVC resin, was purchased from Xinjiang Zhongtai Chemical Co., Ltd.;
[0040] Ethylene-vinyl alcohol copolymer, E171A, was purchased from Jiabo Plastics (Shanghai) Co., Ltd.;
[0041] Glass fiber, fiber length 25-300 μm, provided by Shaoguan Haoli Recycling Resources Utilization Co., Ltd.
[0042] Chitosan, 100 kDA, 1000 kDA, 10000 kDA, and 150000 kDA, were purchased from Shaanxi Baohe Biotechnology Co., Ltd.;
[0043] Maleic anhydride (CAS No.: 108-31-6) was purchased from Shandong Xuchen Chemical Technology Co., Ltd.;
[0044] Phenol (CAS No.: 108-95-2), formaldehyde (CAS No.: 50-00-0), and phosphoric acid (CAS No.: 7664-38-2) were purchased from Aladdin;
[0045] Mica powder and kaolin were purchased from Hebei Huayuan Mining Co., Ltd.;
[0046] Antioxidant 1010 was purchased from Dongguan Baoxu Chemical Technology Co., Ltd.;
[0047] Hexadecyltrimethoxysilane (CAS16415-12-6) and vinyltrimethoxysilane YJ-71 were purchased from Shandong Yuanjin New Materials Co., Ltd.
[0048] Example 1
[0049] A glass fiber reinforced plastic is made of the following raw materials in parts by weight: 80 parts of polyvinyl chloride, 20 parts of modified ethylene-vinyl alcohol copolymer, 20 parts of modified phenolic resin, 40 parts of glass fiber, 10 parts of silane-modified mica powder, 5 parts of calcined kaolin, 1 part of antioxidant 1010, and 1.5 parts of vinyl trimethoxy silane.
[0050] The preparation method of the modified phenolic resin comprises:
[0051] (1) Heat phenol and phosphoric acid to 95°C and stir until completely dissolved; (2) Add chitosan and formaldehyde to the above solution (the molar ratio of phenol to formaldehyde is 0.85, and the amount of chitosan added is 2%, the same below). After the addition is complete, heat the reaction solution to 100°C and reflux for 4 hours; (3) Distill the reaction solution under reduced pressure to obtain a modified phenolic resin.
[0052] The modified ethylene-vinyl alcohol copolymer is prepared by melt-blending 2 parts of Mg / Al-LDH and 100 parts of ethylene-vinyl alcohol copolymer.
[0053] The silane-modified mica powder is prepared by a wet process: hexadecyltrimethoxysilane is dissolved in 10 times of ethanol, mica powder is dissolved in 5 times of deionized water, ultrasonically dispersed for 30 minutes, the two are mixed and stirred for reaction, and then washed, filtered and dried to obtain the silane-modified mica powder.
[0054] The Mg / Al-LDH is prepared by a liquid phase co-precipitation method and has a particle size of 20-70 nm.
[0055] The viscosity average molecular weight of the chitosan is 10000 kDa and the degree of deacetylation is 90%.
[0056] Example 2
[0057] A glass fiber reinforced plastic is made of the following raw materials in parts by weight: 60 parts of polyvinyl chloride, 15 parts of modified ethylene-vinyl alcohol copolymer, 10 parts of modified phenolic resin, 20 parts of glass fiber, 5 parts of silane-modified mica powder, 5 parts of calcined kaolin, 0.5 parts of antioxidant 1010, and 1 part of vinyl trimethoxy silane.
[0058] The preparation method of the modified phenolic resin comprises:
[0059] (1) Heat phenol and phosphoric acid to 95°C and stir until completely dissolved; (2) Add chitosan and formaldehyde to the above solution (the molar ratio of phenol to formaldehyde is 0.85, and the amount of chitosan added is 2%, the same below). After the addition is complete, heat the reaction solution to 100°C and reflux for 4 hours; (3) Distill the reaction solution under reduced pressure to obtain a modified phenolic resin.
[0060] The modified ethylene-vinyl alcohol copolymer is prepared by melt-blending 2 parts of Mg / Al-LDH and 100 parts of ethylene-vinyl alcohol copolymer.
[0061] The silane-modified mica powder is prepared by a wet process: hexadecyltrimethoxysilane is dissolved in 10 times of ethanol, mica powder is dissolved in 5 times of deionized water, ultrasonically dispersed for 30 minutes, the two are mixed and stirred for reaction, and then washed, filtered and dried to obtain the silane-modified mica powder.
[0062] The Mg / Al-LDH is prepared by a liquid phase co-precipitation method and has a particle size of 20-70 nm.
[0063] The viscosity average molecular weight of the chitosan is 10000 kDa and the degree of deacetylation is 90%.
[0064] Example 3
[0065] A glass fiber reinforced plastic is made of the following raw materials in parts by weight: 70 parts of polyvinyl chloride, 15 parts of modified ethylene-vinyl alcohol copolymer, 10 parts of modified phenolic resin, 30 parts of glass fiber, 6 parts of silane-modified mica powder, 10 parts of calcined kaolin, 0.5 parts of antioxidant 1010, and 1 part of vinyl trimethoxy silane.
[0066] The preparation method of the modified phenolic resin comprises:
[0067] (1) Heat phenol and phosphoric acid to 95°C and stir until they are completely dissolved; (2) Add chitosan and formaldehyde to the above solution. After the addition, heat the reaction solution to 100°C and reflux for 4 hours; (3) Distill the reaction solution under reduced pressure to obtain a modified phenolic resin.
[0068] The modified ethylene-vinyl alcohol copolymer is prepared by melt-blending 2 parts of Mg / Al-LDH and 100 parts of ethylene-vinyl alcohol copolymer.
[0069] The silane-modified mica powder is prepared by a wet process: hexadecyltrimethoxysilane is dissolved in 10 times of ethanol, mica powder is dissolved in 5 times of deionized water, ultrasonically dispersed for 30 minutes, the two are mixed and stirred for reaction, and then washed, filtered and dried to obtain the silane-modified mica powder.
[0070] The Mg / Al-LDH is prepared by a liquid phase co-precipitation method and has a particle size of 20-70 nm.
[0071] The viscosity average molecular weight of the chitosan is 10000 kDa and the degree of deacetylation is 90%.
[0072] Example 4
[0073] A glass fiber reinforced plastic is made of the following raw materials in parts by weight: 60 parts of polyvinyl chloride, 15 parts of modified ethylene-vinyl alcohol copolymer, 10 parts of modified phenolic resin, 30 parts of glass fiber, 6 parts of silane-modified mica powder, 10 parts of calcined kaolin, 0.5 parts of antioxidant 1010, and 1 part of vinyl trimethoxy silane.
[0074] The preparation method of the modified phenolic resin comprises:
[0075] (1) Heat phenol and phosphoric acid to 95°C and stir until they are completely dissolved; (2) Add chitosan and formaldehyde to the above solution. After the addition, heat the reaction solution to 100°C and reflux for 4 hours; (3) Distill the reaction solution under reduced pressure to obtain a modified phenolic resin.
[0076] The modified ethylene-vinyl alcohol copolymer is prepared by melt-blending 2 parts of Mg / Al-LDH and 100 parts of ethylene-vinyl alcohol copolymer.
[0077] The silane-modified mica powder is prepared by a wet process: hexadecyltrimethoxysilane is dissolved in 10 times of ethanol, mica powder is dissolved in 5 times of deionized water, ultrasonically dispersed for 30 minutes, the two are mixed and stirred for reaction, and then washed, filtered and dried to obtain the silane-modified mica powder.
[0078] The Mg / Al-LDH is prepared by a liquid phase co-precipitation method and has a particle size of 20-70 nm.
[0079] The viscosity average molecular weight of the chitosan is 10000 kDa and the degree of deacetylation is 90%.
[0080] Example 5
[0081] A glass fiber reinforced plastic is made of the following raw materials in parts by weight: 80 parts of polyvinyl chloride, 20 parts of modified ethylene-vinyl alcohol copolymer, 20 parts of modified phenolic resin, 40 parts of glass fiber, 10 parts of silane-modified mica powder, 5 parts of calcined kaolin, 1 part of antioxidant 1010, and 1.5 parts of vinyl trimethoxy silane.
[0082] The preparation method of the modified phenolic resin comprises:
[0083] (1) Heat phenol and phosphoric acid to 95°C and stir until they are completely dissolved; (2) Add chitosan and formaldehyde to the above solution. After the addition, heat the reaction solution to 100°C and reflux for 4 hours; (3) Distill the reaction solution under reduced pressure to obtain a modified phenolic resin.
[0084] The modified ethylene-vinyl alcohol copolymer is prepared by melt-blending 2 parts of Mg / Al-LDH and 100 parts of ethylene-vinyl alcohol copolymer.
[0085] The silane-modified mica powder is prepared by a wet process: hexadecyltrimethoxysilane is dissolved in 10 times of ethanol, mica powder is dissolved in 5 times of deionized water, ultrasonically dispersed for 30 minutes, the two are mixed and stirred for reaction, and then washed, filtered and dried to obtain the silane-modified mica powder.
[0086] The Mg / Al-LDH is prepared by a liquid phase co-precipitation method and has a particle size of 20-70 nm.
[0087] The viscosity average molecular weight of the chitosan is 1000 kDa and the degree of deacetylation is 95%.
[0088] Example 6
[0089] A glass fiber reinforced plastic is made of the following raw materials in parts by weight: 80 parts of polyvinyl chloride, 20 parts of modified ethylene-vinyl alcohol copolymer, 20 parts of modified phenolic resin, 40 parts of glass fiber, 10 parts of silane-modified mica powder, 5 parts of calcined kaolin, 1 part of antioxidant 1010, and 1.5 parts of vinyl trimethoxy silane.
[0090] The preparation method of the modified phenolic resin comprises:
[0091] (1) Heat phenol and phosphoric acid to 95°C and stir until they are completely dissolved; (2) Add chitosan and formaldehyde to the above solution. After the addition, heat the reaction solution to 100°C and reflux for 4 hours; (3) Distill the reaction solution under reduced pressure to obtain a modified phenolic resin.
[0092] The modified ethylene-vinyl alcohol copolymer is prepared by melt-blending 2 parts of Mg / Al-LDH and 100 parts of ethylene-vinyl alcohol copolymer.
[0093] The silane-modified mica powder is prepared by a wet process: hexadecyltrimethoxysilane is dissolved in 10 times of ethanol, mica powder is dissolved in 5 times of deionized water, ultrasonically dispersed for 30 minutes, the two are mixed and stirred for reaction, and then washed, filtered and dried to obtain the silane-modified mica powder.
[0094] The Mg / Al-LDH is prepared by a liquid phase co-precipitation method and has a particle size of 20-70 nm.
[0095] The viscosity average molecular weight of the chitosan is 100 kDa and the degree of deacetylation is 90%.
[0096] The preparation method of the glass fiber reinforced plastic in the above embodiments 1 to 6 comprises the following steps:
[0097] S1, mixing polyvinyl chloride, modified ethylene-vinyl alcohol copolymer and modified phenolic resin to obtain a mixed resin;
[0098] S2, mixing the mixed resin and glass fiber, modified mica powder, kaolin, coupling agent, and antioxidant uniformly, melt-blending and extruding through a twin-screw extruder to obtain the glass fiber reinforced plastic.
[0099] Comparative Example 1
[0100] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that no modified phenolic resin is added.
[0101] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0102] Comparative Example 2
[0103] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that unmodified phenolic resin is used.
[0104] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0105] Comparative Example 3
[0106] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that the modifier chitosan in the modified phenolic resin has a viscosity average molecular weight of 150000 kDa and a deacetylation degree of 85%.
[0107] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0108] Comparative Example 4
[0109] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that the modifier in the modified phenolic resin is maleic anhydride, and the preparation method of the modified phenolic resin is the same, only the modifier is replaced.
[0110] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0111] Comparative Example 5
[0112] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that no modified ethylene-vinyl alcohol copolymer is added.
[0113] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0114] Comparative Example 6
[0115] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that an unmodified ethylene-vinyl alcohol copolymer is used.
[0116] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0117] Comparative Example 7
[0118] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that no glass fiber is added.
[0119] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0120] Comparative Example 8
[0121] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that unmodified mica powder is used.
[0122] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0123] Comparative Example 9
[0124] This comparative example provides a glass fiber reinforced plastic, which is different from Example 1 in that the weight proportions of some components are different, mainly 30 parts of modified ethylene-vinyl alcohol copolymer, 3 parts of modified phenolic resin, and 5 parts of glass fiber, and the other components are the same.
[0125] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 1.
[0126] Comparative Example 10
[0127] This comparative example provides a glass fiber reinforced plastic, which is different from Example 6 in that an unmodified ethylene-vinyl alcohol copolymer is used.
[0128] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 6.
[0129] Comparative Example 11
[0130] This comparative example provides a glass fiber reinforced plastic, which is different from Example 6 in that unmodified mica powder is used.
[0131] The preparation method of the glass fiber reinforced plastic in this comparative example is the same as that in Example 6.
[0132] The properties of the glass fiber reinforced plastics of Examples 1-6 and Comparative Examples 1-11 were measured:
[0133] (1) Notched impact strength
[0134] The sample size is 100mm×3mm×10mm, and a notch with a width of 2mm is made on the sample by a notch sample making machine. The notch impact strength of the sample is tested by a plastic pendulum impact tester in accordance with the national standard GB / T1043.1-2008 "Determination of impact properties of simply supported beams of plastics", with the impact energy set to 75J and the hammer lifting angle set to 150°.
[0135] (2) Tensile strength
[0136] The sample size is 180mm×10mm×3mm. The tensile strength of the sample is tested by a universal material testing machine in accordance with the national standard GBT1040-2006 “Determination of tensile properties of plastics”. The test speed is set to 2mm / min.
[0137] (3) Tensile strength after thermal aging
[0138] The aging treatment is to place the product in an oven at 150°C for 120 hours, and the aging test is to test the tensile strength and impact strength after cooling to room temperature after the aging treatment.
[0139] The test results are shown in Table 1.
[0140] Table 1 Performance test results
[0141]
[0142] It can be seen from Table 1 that the low-temperature impact resistance, tensile strength, and impact resistance and tensile strength after high-temperature aging of the glass fiber reinforced plastics prepared in Examples 1-4 are better than those in Comparative Examples 1-9. The performance difference of Examples 1-4 is mainly due to the different proportions of each group. The overall comprehensive performance of the plastic samples in the examples is better, and they can still maintain good strength and impact resistance in low and high temperature environments.
[0143] The difference between Comparative Example 1 and Example 1 is that no modified phenolic resin is added, and the impact strength at 0°C, the tensile strength at room temperature, the impact strength after 150°C high-temperature aging for 120h, and the impact strength after 150°C high-temperature aging for 120h all decrease significantly; the difference between Comparative Example 2 and Example 1 is that unmodified phenolic resin is used, and the impact strength at 0°C, the tensile strength at room temperature, the impact strength after 150°C high-temperature aging for 120h, and the impact strength after 150°C high-temperature aging for 120h also decrease significantly, but are slightly better than Comparative Example 1; the difference between Comparative Example 3 and Example 1 is that the molecular weight of chitosan used in the modified phenolic resin is very large, and the impact strength at 0°C, the tensile strength at room temperature, and the impact strength after 150°C high-temperature aging for 120h are significantly reduced. The strength and impact strength after high-temperature aging at 150°C for 120h all decreased to a certain extent, but the degree of decrease was lower than that of Comparative Example 2; the difference between Comparative Example 4 and Example 1 is that the modified phenolic resin is modified with maleic anhydride, and the impact strength at 0°C, tensile strength at room temperature, impact strength after high-temperature aging at 150°C for 120h, and impact strength after high-temperature aging at 150°C for 120h are all lower than those of Example 1, but better than Comparative Examples 1-3; the difference between Comparative Example 5 and Example 1 is that no modified ethylene-vinyl alcohol copolymer is added, and the impact strength at 0°C, tensile strength at room temperature, impact strength after high-temperature aging at 150°C for 120h, and impact strength after high-temperature aging at 150°C for 120h all decrease to a certain extent, among which the impact strength at 0°C, The tensile strength at room temperature is better than that of Comparative Examples 1-4, but the high temperature aging performance is not as good as that of Comparative Examples 3 and Comparative Examples 4; the difference between Comparative Example 6 and Example 1 is that unmodified ethylene-vinyl alcohol copolymer is used, and the impact strength at 0°C, tensile strength at room temperature, impact strength after high temperature aging at 150°C for 120h, and impact strength after high temperature aging at 150°C for 120h all decrease to a certain extent, but the overall performance is good, but the tensile strength after high temperature aging decreases more; the difference between Comparative Example 7 and Example 1 is that no glass fiber is added, and the impact strength at 0°C, tensile strength at room temperature, impact strength after high temperature aging at 150°C for 120h, and impact strength after high temperature aging at 150°C for 120h all decrease to a large extent, among which only the impact strength at 0°C The impact strength is slightly better than that of Comparative Example 1, and the other properties are inferior to Comparative Examples 1-6; the difference between Comparative Example 8 and Example 1 is that unmodified mica powder is used, and the impact strength at 0°C, the tensile strength at room temperature, the impact strength after high-temperature aging at 150°C for 120h, and the impact strength after high-temperature aging at 150°C for 120h are slightly reduced, and the overall performance is good; the difference between Comparative Example 9 and Example 1 is that the content of the modified ethylene-vinyl alcohol copolymer, the modified phenolic resin, and the glass fiber varies greatly, exceeding the optimal ratio range, and the impact strength at 0°C, the tensile strength at room temperature, the impact strength after high-temperature aging at 150°C for 120h, and the impact strength after high-temperature aging at 150°C for 120h are seriously reduced, the comprehensive performance is the worst, and the low temperature resistance and high temperature resistance are both poor;The difference between Comparative Example 10 and Example 6 is that the unmodified ethylene-vinyl alcohol copolymer is used, and the impact strength at 0°C, the tensile strength at room temperature, the impact strength after high-temperature aging at 150°C for 120h, and the impact strength after high-temperature aging at 150°C for 120h all decrease to a certain extent, but the tensile strength after high-temperature aging decreases more; the difference between Comparative Example 11 and Example 6 is that the unmodified mica powder is used, and the impact strength at 0°C and the tensile strength at room temperature decrease slightly, and the impact strength after high-temperature aging at 150°C for 120h and the impact strength after high-temperature aging at 150°C for 120h decrease significantly. ;
[0144] The data results of the embodiments and comparative examples show that when no modified phenolic resin or the modified phenolic resin of the present invention is used, no modified ethylene-vinyl alcohol copolymer is used, no glass fiber is used, and the mass ratio (proportion) of the modified ethylene-vinyl alcohol copolymer, the modified phenolic resin and the glass fiber is not within the range defined by the present invention, the prepared plastic cannot simultaneously meet the requirements of having good high temperature resistance and low temperature resistance.
[0145] Although the embodiments of the present description have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present description, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A glass fiber reinforced plastic, characterized in that: The glass fiber reinforced plastic is made of the following raw materials in parts by weight: 60-80 parts of polyvinyl chloride, 10-20 parts of modified ethylene-vinyl alcohol copolymer, 10-20 parts of modified phenolic resin, 20-40 parts of glass fiber, 1-10 parts of modified mica powder, 1-10 parts of kaolin, 0.5-1 parts of antioxidant and 1-2 parts of coupling agent.
2. A glass fiber reinforced plastic according to claim 1, characterized in that: The preparation method of the modified phenolic resin comprises: (1) Add phenol and acid catalyst into a reaction vessel, heat to 90-100°C, and stir until completely dissolved; (2) Add aldehyde and chitosan to the above solution, and then reflux for 2-5 hours; (3) The reaction solution is subjected to reduced pressure distillation to obtain a modified phenolic resin.
3. A glass fiber reinforced plastic according to claim 2, characterized in that: The phenol is phenol or cresol; and / or the acid catalyst includes at least one of oxalic acid, acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, phosphonic acid, benzenesulfonic acid and p-toluenesulfonic acid; and / or the aldehyde is formaldehyde or acetaldehyde.
4. A glass fiber reinforced plastic according to claim 1, characterized in that: The preparation method of the modified ethylene-vinyl alcohol copolymer is as follows: LDH and ethylene-vinyl alcohol copolymer are melt-blended to obtain the modified ethylene-vinyl alcohol copolymer.
5. A glass fiber reinforced plastic according to claim 4, characterized in that: The amount of LDH added to the modified ethylene-vinyl alcohol copolymer is 0.8-3%, and the particle size of the LDH is 1-100 nm.
6. The glass fiber reinforced plastic according to claim 1, characterized in that: The modified mica powder is silane-modified mica powder.
7. A glass fiber reinforced plastic according to claim 6, characterized in that: The silane is one or more of hexadecyltrimethoxysilane, dodecyltrimethoxysilane, aminopropyltriethoxysilane and propyltrimethoxysilane.
8. The glass fiber reinforced plastic according to claim 1, characterized in that: The antioxidant includes any one of a hindered phenol antioxidant, a phosphite antioxidant, and a thioester antioxidant, or a combination of at least two of them.
9. The glass fiber reinforced plastic according to claim 1, characterized in that: The coupling agent is one or both of vinyl trimethoxy silane and vinyl triethoxy silane.
10. A method for preparing a glass fiber reinforced plastic according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing polyvinyl chloride, modified ethylene-vinyl alcohol copolymer and modified phenolic resin to obtain a mixed resin; S2, mixing the mixed resin and glass fiber, modified mica powder, kaolin, coupling agent, and antioxidant uniformly, melt-blending and extruding through a twin-screw extruder to obtain the glass fiber reinforced plastic.
Citation Information
Patent Citations
Low-temperature-resistant, high-strength and high-wear-resistant polyvinyl chloride nano composite material as well as preparation method and application thereof
CN117362868A
Granules special for high-temperature-resistant and impact-resistant rigid polyvinyl chloride corrugated pipe and preparation method thereof
CN117586589A